Pre-service teachers' perceptions of acceptance of mobile technologies in teaching-learning processes. A Case Study - David Caballero-Mariscal (Revista Latinoamericana de Tecnología Educativa)
The pandemic crisis highlighted the need for a technological and digital transformation of the university, a process that has already begun and that has marked a before and after in the incorporation of technologies in the teaching-learning processes. On the other hand, teachers in training are a privileged group as they are at the end of their training process, in contact with active teachers and will be pillars of social training. For this reason, this study aims to analyze the perceptions of trainee teachers at the University of Granada on the acceptance and inclusion of smartphones in teaching and learning processes, as a result of the Covid-19 pandemic crisis. A qualitative methodology (focus group) was implemented with a sample of 16 trainee teachers belonging to the area of social sciences. The results showed an incorporation of technologies in future teachers, the need for the implementation of smartphones, as well as mobile literacy for students and teachers. In the same way, generational differences, the relevance of motivation and perception in usefulness and ease of use of devices are highlighted. It is concluded that there is a need for training actions in teachers and educational centers to provide an effective response to social and educational needs. For this reason, universities, educational institutions and teachers must strive to understand the scope of mobile teaching and the possibilities of smartphones in increasing motivation and the acquisition of basic skills. Future studies are needed to broaden the scope of analysis to different areas and contexts.